Synthesis, Characterization And Biological Activity of N- Thioureidomaleimic Acid and its Complexes with M(III) ions - A. Ahmed, Musa; R. Suliman, Monim; O. Babikerc, Mohamed (Gezira Journal of Engineering and Applied Sciences, 2018)
The N-thioureidomaleimic acid and its complexes with Cr (III) and La(III) ions have been prepared and characterized by using elemental analysis, thermal analysis, spectroscopy (I.R., u.v-vis., 1H NMR, mass) and magnetic susceptibility measurements. The I.R. spectral data suggest that the thiosemicarbazide derivative coordinates to the metal ions as a tridentate ligand through sulfur, nitrogen and oxygen atoms. The thermal behavior of the complexes indicates thermal stabilities up to about 2000C. The free ligand and its metal complexes have been tested in vitro against a number of microorganisms, to assess their antimicrobial properties.